2017
DOI: 10.1111/jnc.13930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and insulin on dopamine transporter activity and expression in rat caudate‐putamen, nucleus accumbens, and midbrain

Abstract: Food restriction (FR) and obesogenic (OB) diets are known to alter brain dopamine transmission and exert opposite modulatory effects on behavioral responsiveness to psychostimulant drugs of abuse. Mechanisms underlying these diet effects are not fully understood. In the present study we examined diet effects on expression and function of the dopamine transporter (DAT) in caudate-putamen (CPu), nucleus accumbens (NAc), and midbrain regions. DA uptake by CPu, NAc or midbrain synapto(neuro)somes was measured in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 89 publications
(143 reference statements)
3
65
0
Order By: Relevance
“…At the same time, the enhanced, but Naspm-insensitive, behavioral response to quinpirole in FR rats indicates that there is likely more than one neuroadaptation contributing to the net effect of FR on DA transmission and behavior. The recently demonstrated increase in D-2 receptor protein expression in NAc synaptoneurosomes of FR rats points to a potential mechanistic basis of the enhanced response to quinpirole (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the enhanced, but Naspm-insensitive, behavioral response to quinpirole in FR rats indicates that there is likely more than one neuroadaptation contributing to the net effect of FR on DA transmission and behavior. The recently demonstrated increase in D-2 receptor protein expression in NAc synaptoneurosomes of FR rats points to a potential mechanistic basis of the enhanced response to quinpirole (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models allow for the investigation of more causal links between obesity and dopamine transmission and have begun to disentangle the effects of an obesogenic diet from adiposity. Short-term and chronic high fat diets (HFDs) as well as diet-induced obesity were shown to reduce D2R-mRNA and protein expression levels ( [96][97][98][99], but see [100]) ( Table 2). An elegant study suggests that diet-induced obesity may be the cause rather than the result of reduced D2R availability [18••].…”
Section: Obesity and Diet-related Dopamine Differencesmentioning
confidence: 99%
“…One study showed reduced D1R signalling when a diet high in saturated, but not monounsaturated fats (palm oil vs. olive oil), was administered [101]. Finally, diet-related changes in dopamine synthesis [108], release [59,102,105] and uptake (DAT) [98,99] have been observed.…”
Section: Obesity and Diet-related Dopamine Differencesmentioning
confidence: 99%
“…In addition to enhancing striatal DA release, insulin also increases dopamine transporter (DAT) trafficking to the plasma membrane via a PI3‐kinase (PI3K) and Akt signaling pathway, thereby increasing overall DAT activity and DA uptake (Carvelli et al ., ; Garcia et al ., ; Schoffelmeer et al ., ; Mebel et al ., ; Jones et al ., ). However, little is known about how opposite changes in circulating plasma insulin levels with FR vs. OB diets in vivo influence striatal DAT activity in intact, ex vivo striatal slices and DAT responsiveness to acute insulin exposure.…”
Section: Introductionmentioning
confidence: 97%